N6-methyladenosine mediates the cellular proliferation and apoptosis via microRNAs in arsenite-transformed cells. (August 2018) - Gu, Shiyan; Sun, Donglei; Dai, Huangmei; Zhang, Zunzhen
Highlights: M 6 A is involved in the cellular proliferation and apoptosis induced by arsenite. M 6 A level is synergistically controlled by its methyltransferases and demethylase. M 6 A regulates the cellular proliferation and apoptosis via mediating microRNAs. Abstract: N 6 -methyladenosine (m 6 A) modification is implicated to play an important role in cellular biological processes, but its regulatory mechanisms in arsenite-induced carcinogenesis are largely unknown. Here, human bronchial epithelial (HBE) cells were chronically treated with 2.5 μM arsenite sodium (NaAsO2 ) for about 13 weeks and these cells were identified with malignant phenotype which was demonstrated by increased levels of cellular proliferation, percentages of plate colony formation and soft agar clone formation, and high potential of resistance to apoptotic induction. Our results firstly demonstrated that m 6 A modification on RNA was significantly increased in arsenite-transformed cells and this modification may be synergistically regulated by methyltransferase-like 3 (METTL3), methyltransferase-like 14 (METTL14), Wilms tumor 1-associated protein (WTAP) and Fat mass and obesity-associated protein (FTO). In addition, knocking down of METTL3 in arsenite-transformed cells can dramatically reverse the malignant phenotype, which was manifested by lower percentages of clone and colony formation as well as higher rates of apoptotic induction. Given the critical roles of miRNAs in cellular proliferation and apoptosis, miRNAs regulated by m 6 A in arsenite-transformed cells were analyzed by Venn diagram and KEGG pathway in this study. The results showed that these m 6 A-mediated miRNAs can regulate pathways which are closely associated with cellular proliferation and apoptosis, implicating that these miRNAs may be the critical bridge by which m 6 A mediates dysregulation of cell survival and apoptosis in arsenite-transformed cells. Taken together, our results firstly demonstrated the significant role of m 6 A in the prevention of tumor occurrence and progression induced by arsenite.